GSK-J4, a Specific Histone Lysine Demethylase 6A Inhibitor, Ameliorates Lipotoxicity to Cardiomyocytes via Preserving H3K27 Methylation and Reducing Ferroptosis - Xu, Kai; Liu, Xiang; Wen, Bin; Liu, Yazhou; Zhang, Wei; Hu, Xiaolin; Chen, Ling; Hang, Weijian; Chen, Juan (Frontiers in Cardiovascular Medicine, 2022)
Changes of modern lifestyle provokes series metabolic stresses such as hyperlipidemia. Excessive free fatty acids induce cardiomyocyte metabolic reprograming and rearrangement of lipid content of cardiomyocyte, and promotes oxidative stress. As a newly defined lipid peroxidation related cell death pathway, the role of ferroptosis in metabolic stress induced cardiomyocyte injury are poorly revealed. Our work indicates that GSK-J4, a histone lysine demethylase 6A/6B dual inhibitor, can alleviate palmitic acid (PA) induced hypersensitivity to ferroptosis by suppressing H3K27 demethylation. Mechanistically, PA stimulation reduces H3K27me3 level and hence promotes the expression of ACSL4, a key lipid modulator of ferroptosis. GSK-J4 pretreatment significantly preserves H3K27me3 level and reduces ACSL4 level. GSK-J4 also reduces reactive oxygen species to alleviate oxidative stress, which further decrease lipid peroxidation. Taken together, our data suggest that cardiomyocyte undergoes epigenetic reprogramming under metabolic challenges, rearranging of lipid content and sensitizing to ferroptosis. GSK-J4 can be a potential drug in treating hyperlipidemia induced cardiomyocyte injury by targeting at epigenetic modulations.